2019
DOI: 10.1101/840538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative analysis of the physiological contributions of glucose to the TCA cycle

Abstract: The carbon source for catabolism in vivo is a fundamental question in metabolic physiology. Limited by data and rigorous mathematical analysis, controversy exists over the nutritional sources for carbon in the tricarboxylic acid (TCA) cycle under physiological settings. Using isotope-labeling data in vivo across several experimental conditions, we construct multiple models of central carbon metabolism and develop methods based on metabolic flux analysis (MFA) to solve for the preferences of glucose, lactate, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(29 reference statements)
1
11
1
Order By: Relevance
“…Isotope-based labeling studies have attempted to delineate the source of carbon atoms to the TCA cycle in both in vitro and in vivo model systems. For example, some studies have reported that certain tissues and tumors prefer lactate over other substrates as a source of energy(31)(32)(33), while other studies have pinpointed glucose rather than lactate as the predominant contributor to the TCA cycle in most tissues(30,34). Our data do not support that lactate or acetate can be utilized by cells instead of pyruvate to support TCA cycle anaplerosis (Supplemental…”
contrasting
confidence: 81%
See 2 more Smart Citations
“…Isotope-based labeling studies have attempted to delineate the source of carbon atoms to the TCA cycle in both in vitro and in vivo model systems. For example, some studies have reported that certain tissues and tumors prefer lactate over other substrates as a source of energy(31)(32)(33), while other studies have pinpointed glucose rather than lactate as the predominant contributor to the TCA cycle in most tissues(30,34). Our data do not support that lactate or acetate can be utilized by cells instead of pyruvate to support TCA cycle anaplerosis (Supplemental…”
contrasting
confidence: 81%
“…Thus, we argue that bioenergetic collapse, together with reduced pyruvate flux to the TCA cycle, accounts for the dramatic antineoplastic efficacy of HEX against ENO1-deleted gliomas and that glutamine oxidation may not be obligatory for tumor sustenance in vivo.Our study addresses one of the outstanding controversies in the field: What is the predominant source of carbon atoms for the TCA cycle in cancer cells? Although multiple studies have offered unquestionable evidence that excessive glucose flux and oxidation are near-universal characteristics of cancer cells, the net contribution of different carbon sources such as glucose, glutamine, lactate, and acetate is still an unresolved question(29,30). Isotope-based labeling studies have attempted to delineate the source of carbon atoms to the TCA cycle in both in vitro and in vivo model systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we will briefly discuss (1) the meaning of a stable isotope tracer and its enrichment; (2) two basic tracer models for assessing various aspects of metabolic kinetics; and (3) calculations of glucose kinetics in different biological states. More comprehensive and detailed information is available elsewhere [15,16,[40][41][42][43].…”
Section: Basic Principles Of Stable Isotope Tracer Methodologymentioning
confidence: 99%
“…The figure was created with BioRender.com www.e-enm.org 739 cific intracellular metabolic pathways such as glycolysis, mitochondrial tricarboxylic acid [TCA] cycle and pentose pathways within that tissue, etc.) [42,91,92], additional techniques (e.g., deoxyglucose injection, arteriovenous balance, and tissue biopsy for intracellular metabolite labeling) [93,94] may be required. In the fed state such as following a meal intake or a test glucose dose during an oral glucose tolerance test (OGTT), the liver and kidneys become net consumers of plasma glucose.…”
Section: Calculations Of In Vivo Glucose Kineticsmentioning
confidence: 99%